2017
DOI: 10.1038/srep44292
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of extreme cooperation via shared dysphoric experiences

Abstract: Willingness to lay down one’s life for a group of non-kin, well documented historically and ethnographically, represents an evolutionary puzzle. Building on research in social psychology, we develop a mathematical model showing how conditioning cooperation on previous shared experience can allow individually costly pro-group behavior to evolve. The model generates a series of predictions that we then test empirically in a range of special sample populations (including military veterans, college fraternity/soro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
213
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 177 publications
(235 citation statements)
references
References 62 publications
8
213
3
2
Order By: Relevance
“…These findings stand in contrast to the emphasis placed on the role of negative experiences in promoting identity fusion bonds , which has received support from some recent empirical studies (Jong et al, 2015;Whitehouse et al, 2017). Crucially, we observed no comparable relationship between negative affect scores and identity fusion (H2b), nor was the negative affect measure predictive of any pro-group sacrifice outcomes.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…These findings stand in contrast to the emphasis placed on the role of negative experiences in promoting identity fusion bonds , which has received support from some recent empirical studies (Jong et al, 2015;Whitehouse et al, 2017). Crucially, we observed no comparable relationship between negative affect scores and identity fusion (H2b), nor was the negative affect measure predictive of any pro-group sacrifice outcomes.…”
Section: Discussioncontrasting
confidence: 98%
“…Similarly, Newson et al's (2016) study of devoted football fans revealed that experiences of both positive and negative 'key group events' (p. 1) were associated with higher levels of identity fusion. 679-680) and Whitehouse et al (2017) stresses a mediated relationship between negative, potentially traumatic, experiences and identity fusion. The 'shared dysphoria pathway to fusion' model outlined in Whitehouse and Lanman (2014, pp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An especially potent mode of group affiliation, highlighted in the recent literature, is identity “fusion” – in which the boundary between group and self is porous, and the individual experiences a “visceral feeling of ‘oneness’ with the group” (Swann & Buhrmester, 2015). Recent work has demonstrated that identity fusion is a powerful motivator of personally costly, progroup behaviors (Whitehouse, McQuinn, Buhrmester, & Swann, 2014; Whitehouse et al., 2017). For example, strongly fused individuals report more willingness to fight and die for their groups (Swann et al., 2014); are especially inclined to endorse sacrificing their lives for fellow in‐group members (but not out‐group members) in trolley dilemma scenarios (Swann, Gomez, Huici, Morales, & Hixon, 2010); and are especially likely to donate personal funds to support group members in difficulty (Buhrmester, Fraser, Lanman, Whitehouse, & Swann, 2015; Swann, Gomez, Dovidio, Hart, & Jetten, 2010).…”
Section: Introductionmentioning
confidence: 99%